2022
DOI: 10.1542/hpeds.2022-006578
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of Deimplementing High-Flow Nasal Cannula in Pediatric Bronchiolitis

Abstract: BACKGROUND AND OBJECTIVES: High-flow nasal cannula (HFNC) in children hospitalized with bronchiolitis does not significantly improve clinical outcomes but can increase costs and intensive care unit use. Given widespread HFNC use, it is imperative to reduce use. However, there is limited information on key factors that affect deimplementation. To explore acceptability of HFNC deimplementation, perceptions of HFNC benefits, and identify barriers and facilitators to deimplementation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…This high baseline is likely the result of differences in institutional practice and culture surrounding HFNC utilization, as demonstrated by a prior institutional study on understanding the acceptability of HFNC deimplementation. 14 Providers described discomfort with not intervening and the perception that HFNC helps patients appear more comfortable. We hypothesized that the utilization of HFNC at our institution had become synonymous with hospitalization for bronchiolitis, resulting in a cycle of increasing utilization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This high baseline is likely the result of differences in institutional practice and culture surrounding HFNC utilization, as demonstrated by a prior institutional study on understanding the acceptability of HFNC deimplementation. 14 Providers described discomfort with not intervening and the perception that HFNC helps patients appear more comfortable. We hypothesized that the utilization of HFNC at our institution had become synonymous with hospitalization for bronchiolitis, resulting in a cycle of increasing utilization.…”
Section: Discussionmentioning
confidence: 99%
“…Results showed that a majority of providers found the deimplementation of HFNC acceptable. 14 We used barriers and facilitators identified from this study to aid in developing key drivers and targeted interventions. This study grouped barriers to deimplementation into themes: discomfort with not intervening, the perception that HFNC has nonevidence-based clinical benefit, and variation in risk tolerance and clinical experience.…”
Section: Methodsmentioning
confidence: 99%
“…Because of the favoring evidence in these patient groups, the use of HFNC has expanded beyond neonatal respiratory support and bronchiolitis treatment in pediatrics. Simultaneously, there is ongoing effort to reduce the overuse of HFNC in acute bronchiolitis [ 10 , 11 ]. There are no previous systematic summaries about HFNC use as primary respiratory support for other indications in the pediatric population.…”
Section: Introductionmentioning
confidence: 99%